PANDA: A case-study examining a successful Audiology and Otology Patient and Public Involvement and Engagement research group - Laura Boddy; Richard Allen; Rosalyn Parker; Margaret O'Hara; Amy Gosling (The Beryl Institute, 2020)
There has been increasing involvement of patients and members of the public in research; however, case studies describing patient research groups with hearing loss are non-existent. Such case studies will be valuable, enabling evidence-based dialogue and promoting best practice in the engagement of patients, the public and researchers. This paper aims to discuss this practice. The absence of such dialogue may hinder initial efforts by researchers to realise the potential of Patient and Public Involvement. The objective of this study was to set up and run a patient and public involvement and engagement group in audiology research, use the lessons learnt to provide a guide to others in a similar situation, and prompt the dialogue referred to above. A successful group with over 70 members has been set up, with an average attendance for meetings of between 15 and 20 participants. Feedback from the group indicates that members are happy with, and benefit from, their involvement and particularly appreciate the concern of those managing the group better to accommodate sensory impairments. Additionally, the group has improved research output for specific grant applications. We conclude that although this case study contains elements unique to the setting (a large NHS Trust in the Midlands), it also provides transferable observations and resources that can be adapted and utilised by researchers working with patients and the public with hearing loss. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.